Economic of farm management in India - "Kahlon, A.S." (New Delhi, 1981)
Farm management as a distinct discipline in the sense of business management of a farm has come to its own, at least in the highly developed economics. The developing countries have some farm management taught at the universities, but very few of them have developed adequate teaching and research programmes in farm management with substantial professional orientation to economics. The Indian situation is no different.
Keywords: Farm produce